Cytokine Imprint in Preeclampsia - Stefańska, Katarzyna; Zieliński, Maciej; Jankowiak, Martyna; Zamkowska, Dorota; Sakowska, Justyna; Adamski, Przemysław; Jassem-Bobowicz, Joanna; Piekarska, Karolina; Leszczyńska, Katarzyna; Świątkowska-Stodulska, Renata; Kwiatkowski, Sebastian; Preis, Krzysztof; et al. (Frontiers in Immunology, 2021)
The hallmark of preeclampsia (PE) is a shift toward persistent inflammatory response, accompanied by endothelial dysfunction. The driving forces in PE are proinflammatory cytokine and growth factors, in parallel with reduced functionality of anti-inflammatory effectors, like regulatory T cells are observed. Unfortunately, no conclusive mechanism underlying preeclampsia has been identified. For this reason, research on preeclampsia is needed to provide a state of the art understanding of the pathophysiology, identification of new diagnostics tools and the development of targeted therapies. The 68 patients were divided into three groups: gestational hypertension (GH) group (n = 19) and PE group (n = 28) and a control group (n=21). We have tested a set of 53 cytokines, chemokines and growth factors in preeclampsia and gestational hypertension, and then compared them with normal pregnancies. Using a diagnostic test assessment characteristic parameters (IL-22, MDC/CCL22, IL-2/IL-4 ratio) have been identified and cut-off values have been proposed to diagnose preeclampsia. All parameters had high negative or positive predictive values, above 80%. In conclusion, we have proposed a potential set of immune parameters to diagnose preeclampsia.